Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve [tex]\(\log_3 \frac{1}{\sqrt{27}}\)[/tex], we can follow several steps using the properties of logarithms and exponents.
1. Simplifying the Expression Inside the Logarithm:
First, note that [tex]\(27\)[/tex] can be written as a power of 3:
[tex]\[ 27 = 3^3 \][/tex]
Next, let's rewrite [tex]\(\frac{1}{\sqrt{27}}\)[/tex] in terms of powers of 3. The square root of 27 is:
[tex]\[ \sqrt{27} = \sqrt{3^3} = 3^{3/2} \][/tex]
Thus, [tex]\(\frac{1}{\sqrt{27}}\)[/tex] can be expressed as:
[tex]\[ \frac{1}{\sqrt{27}} = \frac{1}{3^{3/2}} = 3^{-3/2} \][/tex]
2. Applying the Logarithm Properties:
Now we need to find [tex]\(\log_3 (3^{-3/2})\)[/tex]. To do this, we use the property of logarithms that states:
[tex]\[ \log_b (a^c) = c \cdot \log_b (a) \][/tex]
Here, [tex]\( a = 3 \)[/tex], [tex]\( c = -3/2 \)[/tex], and the base [tex]\( b = 3 \)[/tex]. Applying this property:
[tex]\[ \log_3 (3^{-3/2}) = -\frac{3}{2} \cdot \log_3 (3) \][/tex]
3. Evaluating Basic Logarithm:
We know that [tex]\(\log_3 (3) = 1\)[/tex] because the logarithm of a number with its own base is always 1.
4. Final Calculation:
Substituting [tex]\(\log_3 (3) = 1\)[/tex] into our equation:
[tex]\[ \log_3 (3^{-3/2}) = -\frac{3}{2} \cdot 1 = -\frac{3}{2} \][/tex]
Thus, the value of [tex]\(\log_3 \frac{1}{\sqrt{27}}\)[/tex] is [tex]\(-1.5\)[/tex].
1. Simplifying the Expression Inside the Logarithm:
First, note that [tex]\(27\)[/tex] can be written as a power of 3:
[tex]\[ 27 = 3^3 \][/tex]
Next, let's rewrite [tex]\(\frac{1}{\sqrt{27}}\)[/tex] in terms of powers of 3. The square root of 27 is:
[tex]\[ \sqrt{27} = \sqrt{3^3} = 3^{3/2} \][/tex]
Thus, [tex]\(\frac{1}{\sqrt{27}}\)[/tex] can be expressed as:
[tex]\[ \frac{1}{\sqrt{27}} = \frac{1}{3^{3/2}} = 3^{-3/2} \][/tex]
2. Applying the Logarithm Properties:
Now we need to find [tex]\(\log_3 (3^{-3/2})\)[/tex]. To do this, we use the property of logarithms that states:
[tex]\[ \log_b (a^c) = c \cdot \log_b (a) \][/tex]
Here, [tex]\( a = 3 \)[/tex], [tex]\( c = -3/2 \)[/tex], and the base [tex]\( b = 3 \)[/tex]. Applying this property:
[tex]\[ \log_3 (3^{-3/2}) = -\frac{3}{2} \cdot \log_3 (3) \][/tex]
3. Evaluating Basic Logarithm:
We know that [tex]\(\log_3 (3) = 1\)[/tex] because the logarithm of a number with its own base is always 1.
4. Final Calculation:
Substituting [tex]\(\log_3 (3) = 1\)[/tex] into our equation:
[tex]\[ \log_3 (3^{-3/2}) = -\frac{3}{2} \cdot 1 = -\frac{3}{2} \][/tex]
Thus, the value of [tex]\(\log_3 \frac{1}{\sqrt{27}}\)[/tex] is [tex]\(-1.5\)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.